Critical perspectives on migrants, migration, and COVID-19 vaccination editorial for special issue - Denise L. Spitzer; Anne-Sophie Jung; Sally Hargreaves (Journal of Migration and Health)
The COVID-19 pandemic has exposed—and exacerbated—major health inequities around the globe including amongst many persons framed as ‘migrants whose lives are shaped by discursive legal, political, and social meanings and legal statuses that situate them within local, national, and global hierarchies. This special issue is dedicated to critical analyses of the roll-out of COVID-19 vaccinations in relation to migrants and other minorities associated with migration, and how migrant groups have been considered and neglected by national and global COVID-19 responses. Drawing from work with asylum seekers, internal and international migrants—both documented and undocumented—in countries ranging from Greece, Japan, and India to Thailand and Canada, authors in this special issue apply critical political economic, feminist, and intersectional lenses to examinations of migrants, migration, and COVID-19 vaccinations.